Nonlinear pharmacokinetics of factor VIII and its phosphatidylinositol lipidic complex in hemophilia A mice. (2nd January 2014) - Kosloski, Matthew P.; Pisal, Dipak S.; Mager, Donald E.; Balu‐Iyer, Sathy V.
ABSTRACT Factor VIII (FVIII) is an important cofactor in the blood coagulation cascade and its deficiency or dysfunction causes hemophilia A (HA), a bleeding disorder. Replacement with recombinant FVIII is limited by a short half‐life and the development of inhibitory antibodies. A phosphatidylinositol (PI) containing lipid nanoparticle was developed that, when associated with FVIII, reduces immunogenicity and prolongs circulation of the therapeutic protein in HA mice. A multiple dose level pharmacokinetic (PK) study of human free FVIII and its FVIII–PI complex over a clinically relevant range of doses (20, 40 and 200 IU/kg) was conducted in HA mice to investigate linearity of the PK and to determine if the reduced catabolism of FVIII following association with PI particles, previously only observed in the terminal phase following 400 IU/kg, could be extendable over a range of doses. The findings suggest that the disposition of FVIII is best characterized by a two‐compartment model with saturable Michaelis‐Menten elimination. Spontaneous complexation of FVIII with PI particles significantly increases plasma survival of the protein at 20 and 40 IU/kg doses. Human simulations at 40 IU/kg project an increase in the terminal half‐life and the time to reach a minimum therapeutic threshold of 0.01 IU/ml of 5.4 h and 40 h, respectively, compared with free FVIII. Formulation with PI containing lipid particles may represent a viable delivery strategy for improving FVIII therapy. Copyright © 2014 John Wiley & Sons, Ltd.